Enhancing Tilapia Pond Productivity Through Carrying Capacity Engineering in Turunrejo Village, Kendal Regency - Haeruddin, Haeruddin; Mudzakir, Abdul Kohar; Rahman, Arif; Werdani, Riandhita Eri; Prakoso, Kukuh (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
Our community engagement (CE) activity aimed to increase productivity in the Nile tilapia pond managed by POKDAKAN Berkah 2 in Turunrejo Village, Kendal Regency. This was achieved through carrying capacity engineering of ponds, mechanization of facilities, probiotic application, and enhancing the knowledge and skills of cultivators in managing pond water quality to meet the Indonesian National Standard (SNI) for tilapia rearing. Knowledge and skills improvement was facilitated through counseling sessions and technical assistance provided during the Nile tilapia rearing activities at Dempond Berkah 2. The community service team provided support by assisting with the procurement of two water pumps and pump holders, constructing inlet and discharge sluices, supplying 20,000 Nile tilapia fry measuring 2–3 cm, and providing factory feed. Fish stocking was conducted in the morning under optimal conditions: water salinity of 8–10 o/oo, neutral pH, and dissolved oxygen levels exceeding 3 mg/L. Factory feeding began on the 15th day after the fry were released into the pond. The results indicated that the fish grew well due to water quality management that met the standards for tilapia maintenance. This success was attributed to effective management of water and feed quality, as well as the provision of adequate cultivation facilities and infrastructure. Pond productivity exceeded the target of 1.5 tons, contributing to increased income for the farming community and improved knowledge and competence of fish farmers in Good Fish Farming Practices (CBIB).